DESCRIPTION OF FACTORS AFFECTING THE PREGNANT WOMEN'S KNOWLEDGE ABOUT CLASSICAL MUSIC IN PUSKESMAS LUBUK BUAYA PADANG YEAR 2017 - Kudri, Al (Menara Ilmu, 2017)
High risk pregnancy incidence is the highest case in Lubuk Buaya Padang CommunityHealth Center 2017. Data 2015 obtained from the Health Office of Padang City 430 pregnantwomen who are at high risk. Observation results from 10 respondents obtained (80%) high riskpregnant women who do not know what classical music. The study aims to determine thedescription of factors that affect pregnant women's knowledge about classical music in LubukBuaya Padang Community Center in 2017.The type of descriptive research is to describe factors influencing pregnant mother'sknowledge about classical music at Lubuk Buaya Padang Health Center 2017. Sampling datacollection starts on July 3 until July 19, 2017 at Lubuk Buaya Padang Health Center for 15days. The population in this study high risk TM-3 pregnant women who came to visit as manyas 59 people with sample 59 people, the data obtained by Accidental Sampling technique. Thestudy used questionnaires and interviews. Data analysis used univariate analysis by usingcomputerization.The results of the study were high risk pregnant women with low knowledge (59.3%).Low risk pregnant women with low education (84.7%). High risk pregnant women who do notwork (71,2%). High risk pregnant women have an uncomfortable environment (72.9%).Based on research that has been done can be concluded that more than half pregnantwomen TM-3 high-risk low knowledge about classical music, it is expected to health workersto hold a special place to do classical music therapy and provide information about classicalmusic can be notified with the making of posters, liflet so that pregnant women are interestedto get information about classical music further.Keywords: knowledge, occupation, education, environment